Advanced Two Dimensional Spray Painter with Scissor Lift Mechanism - R. , Hariharan; Kumar, Vishal; S. , Sandeep; C. , Arul Murugan; Dipankarkar (International Journal of Psychosocial Rehabilitation, 2024)
Painting is the operation of applying paint to surfaces that are physically contacted and lie in the visual areas. This is done to protect the surface from rust, erosion, decomposition, etc., as well as to have good aesthetics. Different methods of painting systems are used in modern technology, of which one of the most common is spray painting. It is used to produce a uniform coating and an excellent finish. But this can also be a tedious task, and also the spray is hazardous. So the use of advanced systems is needed for spray painting applications. This is because the machine can do the operation precisely, and it also eliminated danger to human health. This project proposes the idea of using a double scissor lift arrangement to lift the paint sprayer in the vertical axis and a lead screwdriver to move it in a horizontal axis. The scissor lift is used because it can be used to achieve a good height and also because it is easily portable. The system is more compact and easy to handle, and also, with the help of electrical implementation, it can be fully automated.